Elaboración y evaluación de bloques nutricionales de sangre y contenido ruminal del camal municipal del cantón Pujilí en la alimentación de cuyes en etapa de engorde - Navarro Monge, Cristian Rolando (2013)
The current research was carried out in order to use alternative raw materials for feeding of guinea pigs at fattening time as experimental part in summer season when the traditional feeding in this case is very scant in that zone and the price in the market has a value that fluctuates from 12 to 18 american dollars. for such effect, as objective was proposed to make and evaluate nutritious blocks with the blood addition and ruminant content of the municipal slaughterhouse from pujili town, cotopaxi province. the research methodology used were: experimental research (were used random design and the duncan full design), the descriptive, experimental and statistics research....